The lost language - Mills, Claudia (Margaret Ferguson Books : Holiday House, 2022)
Two sixth grade best friends named Elizabeth try to navigate changes in their relationship as the domineering Liz, "Lizard," decides that they'll start a school club to revive a dying language in order to impress Betsy's demanding mother, a linguistics professor. When Betsy decides to quietly branch out from the control the two women have over her life by joining the school play, she finds a new set of friends and begins exploring things on her own. As the girls' friendship crumbles, each will have to decide the best way to repair their relationship.